A dummy-run evaluation of postoperative hypofractionated intensity-modulated radiation therapy (POHIM-RT) trials for cervical cancer. (14th October 2020) - Cho, Won Kyung; Kim, Heejung; Park, Won; Kim, Sang-Won; Kim, Jongwon; Lee, Kang Kyu; Oh, Jeong Geun; Yoon, Mee Sun; Song, Ju-Young; Ahn, Ki Jung; Park, Sung Kwang; Choi, Jin Hwa; et al.
Abstract: The postoperative hypofractionated intensity-modulated radiation therapy (POHIM-RT) trial is a phase II study to evaluate toxicity following hypofractionated intensity modulated radiation therapy (IMRT) for cervical cancer. This study describes the results of a benchmark procedure for RT quality assurance of the POHIM-RT trial. Six participating institutions were provided computed tomography for RT planning and an IMRT plan for a sample and were instructed to delineate volumes, create a treatment plan and quality assurance (QA) plan, and submit the results of all procedures. The inter-institutional agreements on RT volume and plan results were evaluated using the kappa value and dice similarity coefficients. The simultaneous truth and performance level estimation (STAPLE) method was employed to generate a consensus target volume. The treatment volumes, organs-at-risk volumes, and results of the RT plan and QA reported by the institutions were acceptable and adhered well to the protocol. In terms of clinical target volume (CTV) delineation, there were differences between the institutions, particularly in vaginal cuff and paracolpium subsites. Consensus CTV was generated from the collected CTVs with the STAPLE method. The participating institutions showed considerable agreement regarding volume, dose and QA results. To improve CTV agreement in CTV, we provided feedback with images of the consensus target volume and detailed written guidelines for specific subsites that were the most heterogeneous.